Peluang dan Tantangan Majelis Taklim pada Era Teknologi Informasi Ditinjau dari Perspektif Sosiologi Dakwah: Studi Kasus Majelis Taklim Jabal Al-Rahma di Perumahan Bukit Lawang Indah - Kurniati Kurniati (Proceedings of International Conference on Da'wa and Communication, 2019)
The existence of majelis taklim still plays an important role in delivering and assisting people entering the era of advancement in information technology. The positive impact of advances in information technology opens opportunities for majors to develop better. The negative impact is a challenge for the Taklim Council in trying to overcome the existing problems. The reason for choosing the perspective of propaganda sociology is because in reality people's lives experience very rapid, progressive changes, and often appear to be symptoms of disintegratis, namely loosening of loyalty to common values. This study aims to analyze the problem of the lack of attendance at the activities of the Taklim Jabal al Rahma Assembly. The research method used is descriptive qualitative approach to the propaganda sociology. Data collection techniques with in-depth interviews as primary data and observation and literature literature as secondary data. This study uses Blumer's symbolic interactionism theory, in which Blumer has 3 main principles, namely meaning, language and thought. The results of the study found that there was a communication between the head of the taklim panel and members of the taklim board and the congregation taklim. The solution is to improve communication and optimize information technology to avoid disintegration which will endanger the continuity of Da'wa in the community itself.